Prevalence of 2.2 per mille of significant hearing loss at school age suggests rescreening after NHS. (August 2016) - Holzinger, Daniel; Weishaupt, Annette; Fellinger, Paul; Beitel, Christoph; Fellinger, Johannes
Abstract: Objectives: The study aims to determine the prevalence of different degrees of significant hearing loss in a complete sample of Austrian school-age children born between 1997 and 2001 living in the federal state of Carinthia and to evaluate the role of Newborn Hearing Screening (NHS) in the identification of later hearing loss. Methods: In Carinthia, all school-age children with significant hearing loss (mean pure tone average in the better ear above 40 dB) are registered by the Department of Education. From five complete birth cohorts from 1997 to 2001 (n = 28.171) all the children with sensorineural hearing loss (n = 61, mean age 10.5, age range 7.5–13.6 years) were assessed for their hearing threshold and level of cognitive functioning. Socio-demographic data, including information about NHS and amplification with hearing devices, were collected from parents and teachers using structured interviews. Results: 2.2 children per thousand (49.2% male) were found to be affected by significant bilateral hearing loss at school age, with 36.1% of them having a moderate hearing loss, 34.4% severe, and 29.5% profound. Fourteen children (23.0%) used cochlear implants. Their mean nonverbal IQ was 93.4 (SD 23.1), including 13.1% of children with intellectual disabilities (IQ < 70). Of those who had undergone NHS (85.2%), 50.0% had passed the screening according to parents' reports. Conclusions: A rate of significant hearing loss in school-age children was observed which was twice the rate found in newborns. Ongoing awareness of late-onset hearing loss to improve identification and hearing screening at school entry are recommended.